Pengaruh Latihan Ball Feeling Dan Latihan Zig-Zag Terhadap Peningkatan Kemampuan Dribbling Bola - Najamuddin, Muhammad Reza; Irfan, Irfan; A, Nurul Musfira; Hudain, Muh. Adnan; Rusli, Rusli (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2025)
This study aims to find out: 1) The effect of ball feeling training on improving dribbling ability. 2) The effect of zig-zag practice on improving ball dribbling ability in students. 3) The difference in the effect of ball feeling training and zig-zag practice on improving ball dribbling ability in students. The population is students of Alfityan Gowa IT Junior High School. The sample used was 20 students, the sampling technique used random sampling and the MSOP (Matched Subject Ordinal Pairing) group division system. Results of the study: (1) There is an effect of ball feeling practice on improving ball dribbling ability in students, the average score is 20.6220 to 16.6560 with a observation value of 15.926 > ttable 2.262 and a significant value of 0.000 < α0.05.; (2) There was an effect of zig-zag practice on improving ball dribbling ability in students, the average score was 20.5720 to 15.0020 with an observation t-value of 14.595 > ttable 2.262 and a significant value of 0.000 < α0.05.; (3) There is an effect of the difference between ball feeling training and zig-zag practice on improving ball dribbling ability in futsal extracurricular students of Alfityan Gowa IT Junior High School with a difference value of 16.6560 < 15.0020 with an observation t value of 4.295 > ttable 2.101 and a significant value of 0.000 < α0.05. The conclusion that zig-zag exercises have a greater influence compared to ball feeling exercises on improving ball dribbling ability in futsal extracurricular students of Alfityan Gowa IT Junior High School.